Long term viability of Neurospora crassa at the FGSC - K McCluskey (Fungal Genetics Reports, 2000)
Lyophilized samples of Neurospora crassa were tested following storage for many years. The oldest viable stock was preserved in 1946. Some samples that were preserved more recently were not viable. The characteristics that predispose a sample to viability remain unknown.